Trust of Italian healthcare professionals in covId-19 (anti-sars-cov-2) vaccination - Di Valerio, Z.; Montalti, M.; Guaraldi, F.; Tedesco, D.; Nreu, B.; Mannucci, E.; Monami, M.; Gori, D. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Vaccination is one of the most effective tools available to Public Health. Its potential usefulness is threatened by the rise of vaccine hesitancy among the general population, which has grown as much as to prompt the World Health Organization to express its concerns on the matter. The risk posed by vaccine hesitancy is even more concerning in the light of the efforts to curb the ongoing COVID-19 pandemic, which focus mainly on mass vaccination campaigns. This holds especially true when applied to healthcare professionals, among whom vaccine hesitancy can be particularly detrimental. For these reasons, our study focuses on potential determinants of vaccine hesitancy among healthcare professionals.Study design. The study is a cross-sectional study. Methods. Data were collected from January 1st to February 16th, by means of a self-administered online questionnaire in a cohort of Italian healthcare professionals. Results. Overall, 10,898 questionnaires were collected. Among the respondents, 1.1% expressed vaccine hesitancy. Hesitancy was less frequent in professionals involved in Primary Care and in the Clinical Sciences/Public Health group. Among clinicians, paediatricians, oncologists, and geriatrists showed especially accepting attitudes towards vaccination. Lower hesitancy rates were also registered among the respondents who already had received influenza vaccination and who never had any adverse effects following vaccination. Higher hesitancy rates were observed among individuals who had family members aged >65 years and with a history of severe adverse reactions to vaccination. Conclusion. Vaccine hesitancy rates were extremely low among participants in our study. Some medical specialties shown were particularly accepting towards vaccination. The potential predictors and protective factors pointed out by our analysis might allow more refined targets